Flow investigation in cardiovascular system - Ng, Bernard Thiam Hock. (2008)
The focus of this thesis is to investigate the flow fields in an abdominal aortic aneurysm (AAA) model and the relative flow patterns between the blades of a centrifugal blood pump model.